2010
DOI: 10.3389/fnbeh.2010.00182
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognition in Borderline Personality Disorder: Evidence for Disturbed Recognition of the Emotions, Thoughts, and Intentions of others

Abstract: Disturbed relatedness is a core feature of borderline personality disorder (BPD), and impaired social cognition or deficits in “mentalization” are hypothesized to underlie this feature. To date, only weak empirical evidence argues for impairment in the recognition of emotions, thoughts, or intentions in BPD. Data from facial emotion recognition research indicate that these abilities are altered in BPD only if tasks are complex. The present study aims to assess social cognitive abilities in BPD. Sixty-four wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
224
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 215 publications
(251 citation statements)
references
References 70 publications
21
224
5
1
Order By: Relevance
“…However, the average MASC score observed in our nonclinical adult sample, as well as in its sub-groups based on gender, was markedly lower than the average MASC scores reported in the literature for healthy controls (e.g., Dziobek et al, 2006;Dziobek et al, 2011;Lahera et al, 2014;Preissler et al, 2010). This finding may be explained by linguistic differences and cultural differences in social interaction between Italy and other European countries; however, it is also possible that this finding reflects the use of community dwelling (i.e.…”
Section: Psychometric Characteristics and Normative Data Of The Masccontrasting
confidence: 53%
See 3 more Smart Citations
“…However, the average MASC score observed in our nonclinical adult sample, as well as in its sub-groups based on gender, was markedly lower than the average MASC scores reported in the literature for healthy controls (e.g., Dziobek et al, 2006;Dziobek et al, 2011;Lahera et al, 2014;Preissler et al, 2010). This finding may be explained by linguistic differences and cultural differences in social interaction between Italy and other European countries; however, it is also possible that this finding reflects the use of community dwelling (i.e.…”
Section: Psychometric Characteristics and Normative Data Of The Masccontrasting
confidence: 53%
“…the MASC performance) in NPD and deficits in BPD compared to healthy controls. A significant association between BPD features and hypermentalizing was consistently observed in adolescent inpatients (Sharp et al, 2011, but this finding was not replicated in adult women suffering from BPD, although they showed a significantly lower the MASC total score than healthy comparison women (Preissler et al, 2010).…”
Section: Open Questionsmentioning
confidence: 81%
See 2 more Smart Citations
“…Previous findings regarding empathy in BPD have been conflicting: some studies showed that patients exhibit less empathy compared to controls (Minzenberg et al, 2006;Preißler et al, 2010;Fertuck et al, 2009), while others found evidence for heightened empathy (Franzen et al, 2011;Dinsdale and Crespi, 2013) in patients. Although this conflicting pattern has been explained by referring to the different domains of empathy that show reduced cognitive empathy in BPD patients with unchanged or even heightened affective empathy (reviewed in Dinsdale and Crespi, 2013), here we found that even the affective domain of empathy may be reduced, possibly reflecting a compensatory response in order to protect from emotional contagion through the emotions of others that has been found in BPD (Dinsdale and Crespi, 2013).…”
Section: Discussionmentioning
confidence: 95%